Bench Press Load-Velocity Profiles and Strength After Overload and Taper Microcyles in Male Powerlifters. Issue 12 (December 2020) - Williams, Tyler D.; Esco, Michael R.; Fedewa, Michael V.; Bishop, Phillip A.
Abstract : Abstract: Williams, TD, Esco, MR, Fedewa, MV, and Bishop, PA. Bench press load-velocity profiles and strength after overload and taper microcyles in male powerlifters. J Strength Cond Res 34(12): 3338–3345, 2020—The purpose of this study was to quantify the effect of an overload microcycle and taper on bench press velocity and to determine if the load-velocity relationship could accurately predict 1-repetition maximum (1RM). Twelve male powerlifters participated in resistance training structured into an introduction microcycle, overload microcycle (PostOL), and taper (PostTP). At the end of each microcycle, subjects completed a bench press for 1RM assessment consisting of warm-up sets at 40, 55, 70, and 85% of a previously established 1RM. The mean concentric velocity (MCV) was recorded during each warm-up set. A predicted 1RM (p1RM) was calculated using an individualized load-velocity profile (LVP). The average MCV decreased after PostOL (0.66 ± 0.07 m·s −1 ) compared with baseline (BL) ( p = 0.003; 0.60 ± 0.11 m·s −1 ) but increased after PostTP (0.67 ± 0.09 m·s −1 ). One-repetition maximum increased from PostOL (146.7 ± 19.8 kg) to PostTP ( p = 0.002; 156.1 ± 21.0 kg), with no differences observed between other test sessions ( p > 0.05). Bland-Altman analysis indicated that p1RM was consistently higher than measured 1RM (3.4–7.8 kg), and the limits of agreement were extremely wide. However, very large to near perfect correlations ( r = 0.89 to 0.96) were observed between p1RM and 1RM during BL, PostOL, and PostTP. The load-velocity relationship established from submaximal sets did not accurately predict 1RM, but MCV was affected by changes in weekly training loads. Velocity-based measurements seem to be more sensitive to changes in training loads than maximal strength.